The Socio-Religious Impact of Peer Educators of Women Sexual Workers In The Localization of Krian-Ngadiluwih, Kediri Regency - Sardjuningsih Sardjuningsih (Didaktika Religia, 2020)
This article reveals the relationship between the role of peer educators in the socio-religious awareness of Women Sexual Workers (WPS) in Krian Village, Ngadiluwih, Kediri Regency. Peer educator is a solution from the Regional Government that is given to WPS who are considered to have strengths and abilities in peer communication. The main objective is to prevent HIV/AIDS in the area of localization. There is no denying that WPS always get negative stigma from the community. Moreover, localization has always been the most vulnerable point in the spread of sexually transmitted diseases (STDs) such as HIV/AIDS. Therefore, the Regional Government held a peer educator program so that the socialization of the dangers of the disease could be disseminated through fellow WPS. This article was prepared with a qualitative-descriptive methodology of the phenomenological study type. Data were collected through observation and interviews with a number of key respondents. This article concludes that peer educators work using a personal approach, promoting friendship, kinship, and empathy. The peer educator officers felt a personal, interpersonal, and impact on family relationships whereas the forms of diversity of the peer educator officers can be categorized into three, namely symbolic religion, identity religion, and camouflage religion.